The Impact of Political Uncertainty on Asset Prices : The Case of the United Kingdom's EU Membership Referendum. (IMF Working Papers; Working Paper, 2021)
How did expectations of the outcome of the United Kingdom's (UK) referendum on European Union (EU) membership in 2016 affect prices in financial markets? We study this using high frequency data from betting and financial markets. We find that a one percentage point increase in the probability of "Leave" result caused British stocks (FTSE All-Share) to decline by 0.004 percent, and the Pound to depreciate by 0.006 percent against the euro. We find negative and significant effects for most sub-sectors, and negative spill-overs to other EU member countries. We show that the differential impact across sectors and countries can be explained by differences in the trade exposures.